Logistics Industry Readiness in Application Policy Over Dimension Overloading (ODOL) - Darmayanti, Ni Luh; Dwipayana, Arif Devi (ASTONJADRO, 2023)
The existence of vehicles with excess loads and dimensions or called ODOL is a problem that public transport service providers often face. The author compiled this paper to find out indicators of the readiness of the logistics industry in supporting the Zero ODOL policy which will become effective in January 2023. By definition, overload is a condition when a vehicle carries a load that exceeds the specified load limit. While overdimension is a condition when the dimensions of the vehicle carrier do not match production standards and regulatory provisions. This study is a type of qualitative research with a discussion model in the form of data descriptions in verbal form. The data collection technique used is a literacy study derived from secondary data sources. The main focus to be built in this study is to find out the readiness of the logistics industry for implementing ODOL. Broadly speaking, ODOL is not only a transportation problem, but has spread to the socio-economic sector because this problem is prone to occur from upstream to downstream of the logistics process. ODOL causes a domino effect that causes losses of up to IDR 43 trillion every year. In order to realize this policy, readiness indicators are needed. But unfortunately, In order to realize this policy, readiness indicators are needed. But unfortunately, In order to realize this policy, readiness indicators are needed. But unfortunately,the impact resulting from the Zero ODOL policy discourse is considered too heavy for the industry because they are currently struggling to recover after the co-19 pandemic. So we need a recommendation strategy that can optimize policies while minimizing negative impacts on the logistics industry.